The measurement of media literacy in eating disorder risk factor research: psychometric properties of six measures. Issue 1 (December 2016) - McLean, Siân; Paxton, Susan; Wertheim, Eleanor
Abstract Background Evaluation of media literacy-based interventions for the prevention of eating disorder risk is limited by the lack of appropriate measures with established psychometric properties with which to assess change in media literacy. This study aims to fill this gap by examining the psychometric properties and use in eating disorders risk factor research of six measures of media literacy that assess media processing and critical thinking about general media and critical thinking about appearance-focused media. Methods The factor structure, internal consistency, test-retest reliability, and construct validity, including convergent and discriminant validity, were examined in six measures in two samples of early adolescent females. The measures were the Realism Scepticism, Similarity Scepticism, and Desirability Scepticism subscales of the Media Attitudes Questionnaire, the Fake subscale of the Critical Processing of Beauty Images Scale, the Critical Thinking about Media Messages scale, and Critical Thinking about Media Messages - Appearance Focus scale. Results The factor structure of the measures was supported with factor analysis. Items from the Media Attitudes Questionnaire loaded on the three subscales Realism Scepticism, Similarity Scepticism, and Desirability Scepticism and items from each of the Fake subscale, Critical Thinking about Media Messages scale and Critical Thinking about Media Messages - Appearance Focus scale loaded on one scale. In addition, scores on the measures were reliable (adequate internal consistency and test-retest reliability) and valid (adequate construct, convergent, and discriminant validity) in early adolescent females. Two exceptions were Realism Scepticism, which had slightly low test-retest reliability, and the Fake subscale, for which support for construct validity was lacking. Conclusions This study provides evidence to support the use of select media literacy measures, particularly the Realism Scepticism subscale and the Critical Thinking about Media Messages scale, in eating disorder risk factor research and the findings will contribute to enhanced evaluation of media literacy-based prevention interventions.